Transforming Religious Education Through Inclusivity: How Indonesian Pesantren Cultivate Moderate Islamic Values and Da'wah Practices - Asep Iwan Setiawan; Yusuf Zaenal Abidin; Ridwan Rustandi; Ahmad Sarbini; Rohmanur Aziz (Universitas Pesantren Kh abdul Chalim Mojokerto, 2026)
The challenge of religious extremism in multicultural societies demands educational institutions that can cultivate moderate Islamic values and inclusive attitudes. This research investigates how Indonesian pesantren (Islamic boarding schools) transform into inclusive spaces that strengthen religious moderation (wasathiyyah) and moderate da’wah (Islamic propagation) practices. Employing an interpretive paradigm with qualitative methods, this study examines two pesantren models: Pesantren Persatuan Islam Manbaul Huda in Bandung City and Pesantren Welas Asih in Garut Regency through observation, in-depth interviews with pesantren leaders, and document analysis. The findings reveal that pesantren inclusivity is driven by structural factors, particularly government policies promoting wasathiyyah Islam, and cultural factors embedded in institutional management. The cultivation of religious moderation occurs through five interconnected roles of ustaz (Islamic teachers): as conservators, preserving authentic Islamic teachings; as innovators, creating integrated spiritual-nationalism programs; as transmitters, disseminating moderate values; as transformators, modeling exemplary behavior through interfaith learning initiatives; and as organizers, implementing systematic character-strengthening activities. These pesantren successfully produce Muslim cadres with open-minded, wise, moderate perspectives who embody Islam as rahmatan lil alamin (mercy to all worlds), demonstrating that religious education institutions can serve as effective epicenters for cultivating tolerance, justice, and balanced attitudes in addressing Indonesia’s spiritual and cultural plurality.